Pencegahan Radikalisme melalui Implementasi Moderasi Beragama dalam Perspektif Piagam Madinah - Dedi Ardiansyah; Basuki Basuki (Fahima, 2023)
Religious moderation is a program that is currently being promoted by the government to respond and to overcome the problems of radicalism and terrorism. The existence of moderation has been pursued in various spaces, as a tangible manifestation of the Internalisation of a moderate attitude in living the life of society and the state. But it does not rule out the possibility that religious moderation is considered to moderate Islam in its ultimate goal. Photographing the form of religious moderation in the perspective of the Madinah Charter as a form of manifestation of tolerance. This research aims to describe the reflections of the Medina Charter in regulating and managing the state system. In addition, it reveals the dimensions of the Medina Charter, which is full of tolerance and moderate values.